Determination of Poultry Manure on Growth and Fruit Yield of Selected Pepper Species in Nigeria - L. A. Babatola; C. J. Uche (Research Highlights in Agricultural Sciences Vol. 1, 2022)
The objective of the study is to assess the growth and yield of pepper varieties under different application rates of poultry manure and storage qualities of pepper under different storage structures. The production of pepper is low due to decrease in fertility of soil and inadequate storage structures. Pepper contributes substantially to the Nigerian diet. It is a main constituent of soups and stews. Tatase was reported to contain more minerals than others common peppers in Nigeria. A field experiment was carried out at Department of Agronomy, University of Ibadan between November, 2017 and April, 2018 growing season. Two pepper types (Capsicum annum and Capsicum frutescens) were employed in this study, with four different treatments consisting of various quantities of poultry manure. In a totally randomised design, controls of 0 g of poultry manure (T1), 12.5 g (T2), 25 g (T3), and 37.5 g (T4) were spread out and reproduced four times. In June 2018, a storage experiment was conducted in the Department and at the Nigeria Stored Products Research Institute (NSPRI) in Ibadan. The storage experiment comprised of four treatments with ambient condition (open shelf), wet basket, Evaporative Coolant Structure (ECS/Pot-in-pot), and plastic crates used as storage structures, laid out in a completely randomised design and replicated three times. The physical parameters obtained in days in storage (DIS) included weight loss (%), firmness, freshness, among others. Data observed were subjected to analysis of variance (ANOVA) and means separated using least significant difference (LSD) at p>0.05. The result obtained showed that pepper growth was enhanced using Capsicum frutescens under 25 g poultry manure application rate which resulted to superior pepper yield. Increase in the amount of PM applied significantly improved the crude protein, crude fibre and ash content, but did not influence the dry matter. Poultry Manure did not influence dry matter of pepper for the different levels applied. Within two weeks of storage, the combination of pot-in-pot and sawdust as storage structures improved the storage properties of pepper fruits. Although the various manure treatments had no significant effect on pepper postharvest quality, the ECS can be effectively used in the storage of pepper fruits to improve postharvest quality, lengthen shelf life, and increase the commodity’s affordability in all seasons.